LEVERAGING TECHNOLOGY AND AI FOR PERSONALIZED LISTENING PRACTICE IN ENGLISH LANGUAGE TEACHING - Zubaydova Nilufar Neʼmatullayevna; Umurzakova Raykhona (TADQIQOTLAR.UZ, 2024)
Annotation: This article explores the potential of artificial intelligence (AI) and technology  in  personalizing  listening  practice  for  English  language  learners.  By examining  AI-driven  tools,  such  as  speech  recognition  applications  and  virtual teaching assistants, the study highlights how these technologies can customize listening exercises  to  meet  each  learner’s  proficiency  level  and  specific  needs.  The  article discusses the benefits of adaptive learning technologies, such as providing real-time feedback, addressing unique linguistic challenges, and enhancing engagement through tailored  content.  This  analysis  offers  insights  into  how  technology-enabled, individualized  instruction  can  improve  listening  comprehension  skills  and  foster  a more effective, student-centered approach to teaching English.